Golden Circles

Geometry Level 3

Two unit circles C 1 C_1 and C 2 C_2 are placed tangent to a line and to each other. Then circle C 3 C_3 is placed tangent to the line and tangent to circles C 2 C_2 and C 1 C_1 , and circle C 4 C_4 is placed tangent to the line and tangent to circles C 3 C_3 and C 2 C_2 , and so on, so each new circle C n C_n is placed tangent to the line and tangent to circles C n 1 C_{n - 1} and C n 2 C_{n - 2} .

Let A n A_n be the area of each circle C n C_n . Then lim n A n A n + 1 {\displaystyle \lim_{n\to\infty}} \frac{A_{n}}{A_{n + 1}} = ϕ m \phi ^m where ϕ \phi is the golden ratio 1 + 5 2 \frac{1 + \sqrt{5}}{2} and m m is an integer.

What is m m ?


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Jul 26, 2018

Let the radius of circle C n C_n be r n r_n . Then we note that the horizontal distance between centers of C 2 C_2 and C 3 C_3 is equal to the sum of distance between centers of C 2 C_2 and C 4 C_4 and distance between centers of C 3 C_3 and C 4 C_4 and by Pythagorean theorem:

( r 2 + r 3 ) 2 ( r 2 r 3 ) 2 = ( r 2 + r 4 ) 2 ( r 2 r 4 ) 2 + ( r 3 + r 4 ) 2 ( r 3 r 4 ) 2 2 r 2 r 3 = 2 r 2 r 4 + 2 r 3 r 4 Divide both sides by 2 r 2 r 3 r 4 1 r 4 = 1 r 3 + 1 r 2 \begin{aligned} \sqrt{(r_2+r_3)^2-(r_2-r_3)^2}&= \sqrt{(r_2+r_4)^2-(r_2-r_4)^2}+ \sqrt{(r_3+r_4)^2-(r_3-r_4)^2} \\ 2 \sqrt{r_2r_3}&= 2 \sqrt{r_2r_4}+ 2 \sqrt{r_3r_4} \quad \quad \small \color{#3D99F6} \text{Divide both sides by }2\sqrt{r_2r_3r_4} \\ \implies \frac 1{\sqrt{r_4}} &= \frac 1{\sqrt{r_3}} + \frac 1{\sqrt{r_2}} \end{aligned}

Then we have:

1 r 1 = 1 = F 1 where F n is the n th Fibonacci number. 1 r 2 = 1 = F 2 1 r 3 = 1 r 2 + 1 r 1 = 2 = F 3 1 r 4 = 1 r 3 + 1 r 2 = 3 = F 4 1 r n = F n \begin{aligned} \frac 1{\sqrt{r_1}} & = 1 = F_1 & \small \color{#3D99F6} \text{where }F_n \text{ is the }n\text{th Fibonacci number.} \\ \frac 1{\sqrt{r_2}} & = 1 = F_2 \\ \frac 1{\sqrt{r_3}} & = \frac 1{\sqrt{r_2}} + \frac 1{\sqrt{r_1}} = 2 = F_3 \\ \frac 1{\sqrt{r_4}} & = \frac 1{\sqrt{r_3}} + \frac 1{\sqrt{r_2}} = 3 = F_4 \\ \implies \frac 1{\sqrt{r_n}} & = F_n \end{aligned}

Then we have:

lim n A n A n + 1 = lim n π r n 2 π r n + 1 2 = lim n ( r n r n + 1 ) 4 = lim n ( F n + 1 F n ) 4 = φ 4 where φ is the golden ratio. \begin{aligned} \lim_{n\to \infty} \frac {A_n}{A_{n+1}} & =\lim_{n\to \infty} \frac {πr_n^2}{πr_{n+1}^2} \\ & = \lim_{n\to \infty} \left(\sqrt{\frac {r_n}{r_{n+1}}}\right)^4 \\ & = \lim_{n\to \infty} \left(\frac {F_{n+1}}{F_n}\right)^4 \\ & = \varphi^4 & \small \color{#3D99F6} \text{where }\varphi \text{ is the golden ratio.} \end{aligned}

Therefore, m = 4 m=\boxed 4 .

Nice write-up!

David Vreken - 2 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...